Application of the C4.5 Algorithm on the Effect of Watching Youtube Videos On the Development of Early Childhood Creativity - Sintawati, Ita Dewi; Widiarina, Widiarina; Mariskhana, Kartika (Sinkron : jurnal dan penelitian teknik informatika, 2021)
Youtube media is one of the social media for communication used by the community, not out of reach of children. The rapid development of information technology, of course, this has an influence on human life. Talking about life in humans, it cannot be separated from human behavior. Some psychologists say that children tend to fully absorb what they see, and children will learn from what they see. This can trigger creativity for young children. The creativity of each individual can be seen in terms of how he makes something he thinks of because he sees an object that already exists and then he innovates it into a new form. This attracted the attention of the author to identify and describe the impact of watching YouTube videos on the development of early childhood creativity. This type of research is based on developing phenomena, how much influence is brought about by technological advances on YouTube social media in the formation of children's behavior. The process of completing the goals to be achieved in this study is to provide information about recommendations for child development with positive creativity, making it easier to determine early childhood development by using the Decision Tree Algorithm C4,5 method. The problem in this study is that early childhood imaginations are higher and will be affected by streaming video ads on YouTube. The results showed that children aged 3 and 4 years often watched, while children aged 5 and 6 years did not watch often, so the role of parents was more dominant in supervising children aged 3 and 4 years.